Student Motivation and Associated Outcomes: A Meta-Analysis From Self-Determination Theory - Howard, Joshua L.; Bureau, Julien; Guay, Frédéric; Chong, Jane X. Y.; Ryan, Richard M. (Perspectives on psychological science, 2021)
Student outcomes are influenced by different types of motivation that stem from external incentives, ego involvement, personal value, and intrinsic interest. The types of motivation described in self-determination theory each co-occur to different degrees and should lead to different consequences. The associations with outcomes are due in part to unique characteristics and in part to the degree of autonomy each entails. In the current meta-analysis, we examine these different types of motivation in 344 samples (223,209 participants) as they relate to 26 performance, well-being, goal orientation, and persistence-related student outcomes. Findings highlight that intrinsic motivation is related to student success and well-being, whereas personal value (identified regulation) is particularly highly related to persistence. Ego-involved motives (introjected regulation) were positively related to persistence and performance goals but also positively related with indicators of ill-being. Motivation driven by a desire to obtain rewards or avoid punishment (external regulation) was not associated with performance or persistence but was associated with decreased well-being. Finally, amotivation was related to poor outcomes. Relative weights analysis further estimates the degree to which motivation types uniquely predict outcomes, highlighting that identified regulation and intrinsic motivation are likely key factors for school adjustment.